PANDUAN MAQASID SYARIAH UNTUK KONSUMEN SKINCARE: INTEGRASI HALAL, KESEHATAN, DAN KEBERLANJUTAN (Studi Pada pengguna Skincare di Kabupaten Bone) - Herianti, Herianti; Rosmini, Rosmini; Otong Karyono (Bajang Institute, 2024)
This research aims to develop a Maqasid Shariah guideline for skincare consumers in Bone Regency, where the majority of the population is Muslim. The focus is on integrating halal, health, and sustainability aspects in the selection of skincare products. With the increasing awareness of safe and responsible skincare, this guideline is expected to help consumers choose products that are halal, healthy, and environmentally friendly. The research method uses a qualitative approach, combining surveys and in-depth interviews with skincare users in Bone Regency to understand their practices in applying Maqasid Shariah principles. The results show that while many consumers are aware of the importance of halal, there is still a lack of knowledge regarding health and sustainability aspects. This guideline provides structured information on halal criteria, ingredient safety, and sustainability practices that should be considered. These findings are expected to raise awareness and provide recommendations for producers to develop products that meet Maqasid Shariah criteria, supporting the sustainability of an ethical and responsible skincare industry